Hospice care: nurses' experience and perception of older adult patients' experiences - Aeling, Jennifer, author; Chavez, Ernest, advisor; Fruhauf, Christine, committee member; Rickard, Kathryn, committee member; Richards, Tracy, committee member (Colorado State University. Libraries, 2018)
The current study sought to understand the experience of hospice nursing staff with hospice and the differences they perceived in caring for older adult patients who utilize hospice for longer and shorter periods. This study also sought to understand older adult patients' experience of hospice services and if length of hospice stays had an effect on the patients' end-of-life experience, as perceived by hospice nursing staff. Interpretative Phenomenological Analysis (IPA) was used to extract themes and subthemes from 10 interviews conducted with hospice nursing staff. Major themes include nursing staff reporting a positive view of hospice, but also being aware of a perceived stigma against hospice among both older adults and their family members. Another major theme identified was how older adults' perception of hospice changes based on length of use, with longer use leading to more positive views of hospice. Participants discussed aspects that affect length of stay and how longer hospice stays are more positive than shorter. The last two major themes were participants believing more education about hospice is needed and a frustration with the Medicare reimbursement process of hospice. Content analysis was also utilized to extract two noteworthy concepts that did not fit within the guidelines of IPA. These noteworthy concepts were extracted from a comparison of two older adult deaths, one that used hospice for a short period (less than two weeks) and another for a long period (more than four weeks). When comparing these stories, it became evident that longer hospice stays had more aspects of a 'good' death and tended to utilize more services provided by hospice. These themes and noteworthy concepts suggest hospice nursing staff believe longer hospice stays are more positive, hospice nursing staff view hospice more positively than older adult patients, and more education may lead to longer hospice stays.
Keywords: hospice; qualitative; nursing; end of life